Real analysis and probability - Dudley, R. M. (Richard M.) (Cambridge studies in advanced mathematics, 2002)
This classic graduate textbook offers a clear exposition of modern probability theory and of the interplay between the properties of metric spaces and probability measures. The comprehensive historical notes have been further amplified for this new edition, and a number of new exercises have been added, together with hints for solution.